137 Withdrawal of dialysis; end of life considerations and advanced care planning. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Prentice, J; Hetherington, L; Findlay, M; Collidge, T
Abstract : Background: Dialysis withdrawal is the commonest cause of death in patients with end stage renal disease aged >75. Factors contributing the withdrawal have been described but to what degree advanced care planning (ACP) is initiated in unknown. We sought to describe current practice within a large renal unit. Methods: We performed a retrospective analysis of patients who died following dialysis withdrawal from 2015–2017. Patient demographics, markers of health, triggers for withdrawal, admissions, timing and degree of ACP discussions were extracted. Results: 52 patients were included. Median age at death 76 interquartile range (IQR) (70, 81) years. Median duration of dialysis was 42 (IQR 10.5, 75) months with 30.8% dying within one year of commencement of dialysis. Median Charleston co-morbidity score was 8 (IQR 6, 9) with documentation of 'frailty' present in 52% of the cohort. 25% of the patients had an acute event triggering withdrawal. ACP was discussed with 34% of patients with 82% of patients achieving their preferred place of death where this was documented. Median length of last admission was 24 days (IQR 11, 43) compared with 11 days (IQR 0, 55) if the patient had an ACP (p-value 0.736). Conclusion: We are not good at initiating timely ACP in deteriorating dialysis patients despite identifying such patients. With an increasingly frail, multi-morbid population the need for these discussions will increase. Early ACP discussions with frail patients starting dialysis may inform later conversations and improve their quality of care. Encouragingly asking about preferred place of death improved the likelihood of achieving a death in the patients preferred location. Identification of poor prognostic markers such as dementia, introducing staff training in palliative care and adopting routine frailty scoring may guide timely conversations in anticipation of deterioration in vulnerable patient groups.